Spiritual Intelligence as a Mediator between Personality and Emotional and Decisional Forgiveness in Polish Adults - Justyna Mróz; Kinga Kaleta; Katarzyna Skrzypińska (Religions, 2023)
Forgiveness is a constructive method of dealing with interpersonal incidents. It is determined by many factors, including personality and spirituality. The purpose of the present study was to explore the relationships between the Big Five personality traits, spiritual intelligence, and emotional and decisional forgiveness in a real situation. The study involved 396 Polish participants aged from 18 to 79. Four tools were used: the Abridged Big Five-Dimensional Circumplex (AB5C), the Emotional Forgiveness Scale (EFS), the Decision to Forgive Scale (DTFS), and the Spiritual Intelligence Self-Report Inventory (SISRI-24). The results demonstrated that personality traits positively correlated with aspects of spiritual intelligence and two types of forgiveness. Personal meaning production (PMP) and transcendental awareness (TA) mediated the relationship between personality and forgiveness, especially when accompanied by taking the decision to forgive. The ability to find meaning and deeper insight into difficult interpersonal incidents was found to be a possible way of linking personality with the forgiveness of others.